Cutaneous Manifestations in Patients with Chronic Kidney Disease on Maintenance Hemodialysis. (5th July 2012) - Kolla, Praveen Kumar; Desai, Madhav; Pathapati, Ram Mohan; Mastan Valli, B.; Pentyala, Suneetha; Madhusudhan Reddy, G.; Vijaya Mohan Rao, A.
Abstract : Cutaneous disorders can precede or follow the initiation of hemodialysis treatment. We evaluated the prevalence of various dermatological manifestations in patients undergoing hemodialysis at least twice a week for minimum of three months at our center. Patients were excluded if they were undergoing hemodialysis less than twice a week or on hemodialysis secondary to ESRD following graft dysfunction. One hundred and forty-three patients were evaluated. Among them, there were 113 male and 30 females. Among the skin changes, pruritus accounted for 56%, Xerosis was observed in 52%, Diffuse blackish hyper pigmentation was seen in 40%. Skin infections was seen in 53% of patients, of these fungal, bacterial and viral infections were 27.2%, 14.6%, and 11.2%, respectively. Kyrle's disease was observed only in 6.9%. Other skin manifestations include eczema 4.8%, psoriasis 2.7%, and drug rash 2.1%. Nail changes were observed in 46 patients of whom 27 patients had onychomycosis. Other changes include discoloration, onycholysis, and splinter hemorrhages. Hair changes were observed in 21.7%. Mucosal changes were seen in 27.3%. In our study, pruritus, xerosis, and pigmentation were higher among skin changes. Recognition and management of some of these dermatological manifestations vastly reduce the morbidity and improve the quality of life.